2013
DOI: 10.1007/s12032-013-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of apolipoprotein E in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer with a poor prognosis. Our previous proteomic analysis found apolipoprotein E (ApoE) protein to be up-regulated in the sera of patients with PDAC. In this study, we sought to confirm this finding and investigate the relationship between ApoE and PDAC. We measured ApoE expression in tissues from PDAC patients and normal controls (NC) by real-time PCR, western blot, and immunohistochemistry. Enzyme-linked immunosorbent assay (ELISA) was applied to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…With the exception of haptoglobin, for which no significant difference was found, the ratios between the two groups revealed similar characteristics but the ratios were less prominent. The elevated serum apolipoprotein E levels in PaCa patients assessed in this initial study by 2D-DIGE and ELISA are in concordance with a recent study be Chen et al Appling different approaches including ELISA they found an up-regulation of apolipoprotein E in PaCa-tissues and elevated apolipoprotein E levels in PaCa patients serum [40].…”
Section: Discussionsupporting
confidence: 91%
“…With the exception of haptoglobin, for which no significant difference was found, the ratios between the two groups revealed similar characteristics but the ratios were less prominent. The elevated serum apolipoprotein E levels in PaCa patients assessed in this initial study by 2D-DIGE and ELISA are in concordance with a recent study be Chen et al Appling different approaches including ELISA they found an up-regulation of apolipoprotein E in PaCa-tissues and elevated apolipoprotein E levels in PaCa patients serum [40].…”
Section: Discussionsupporting
confidence: 91%
“…S7B, C), which activates MMPs in the hypoxic microenvironment (Sansone et al, ). Since MMPs are angiogenesis promoter in inflammatory tumoural niche (Chen et al, ), we demonstrated that NRs agonists reduced also tube formation in vitro (Supporting information Fig. S8).…”
Section: Resultsmentioning
confidence: 53%
“…19 The final scores were ranged as following: total score < 3 was defined as negative (À), 3e6 as "þ", and >6 as "þþ.'' To analyze the correlation of Prx-1 with tumor angiogenesis, microvessel density (MVD) was measured after staining for CD31.…”
Section: Patients and Samplesmentioning
confidence: 99%